Exploring the interplay between academic and athletic identities among elite student athletes in tertiary education in Ireland - Conor Whelan; Alan Yates (Ozlem Book Center, 2024)
The pursuit of higher education presents unique challenges for elite student-athletes, who must balance academic responsibilities with the demands of athletic performance. Understanding how these individuals manage these dual roles is crucial for developing effective support systems in academic and athletic settings. This study investigated the interplay between academic and athletic identities among elite student-athletes in Ireland, focusing on the influence of motivation and social support. Data were collected using a cross-sectional online survey from 100 elite student-athletes, defined as individuals participating in elite-level sports while enrolled in full-time tertiary education in Ireland. The survey included validated measures of academic identity, athletic identity, motivation, and social support. The results show that the majority of participants identified primarily as student-athletes, with greater emphasis on their academic careers. Motivation was a significant predictor of both academic and athletic identities, while social support had no significant effect. These findings challenge the assumption that elite student-athletes predominantly prioritise their athletic roles and underscore the importance of fostering intrinsic motivation. Institutions are encouraged to implement tailored interventions, such as academic mentorship and flexible academic policies, to support student-athletes in balancing their dual careers. Future research should explore the underlying factors behind the minimal impact of social support and further examine motivation-based interventions.